2015
DOI: 10.1002/bit.25692
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new platform for secretory production of recombinant proteins in Corynebacterium glutamicum

Abstract: Corynebacterium glutamicum, which has been for long an industrial producer of various L-amino acids, nucleic acids, and vitamins, is now also regarded as a potential host for the secretory production of recombinant proteins. To harness its potential as an industrial platform for recombinant protein production, the development of an efficient secretion system is necessary. Particularly, regarding protein production in large-scale bioreactors, it would be appropriate to develop a secretory expression system that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 35 publications
0
55
1
1
Order By: Relevance
“…These recombinant C. glutamicum strains simultaneously hydrolyze biomass and produce biochemicals such as succinate, l ‐lysine, and xylonic acid using released glucose, maltose, cellobiose, d ‐xylose, and l ‐arabinose from biomass (Fig. ) . Systematic engineering of metabolic pathways in C. glutamicum has allowed the biochemical production of novel products, such as platform chemicals (ethanol, ethylene glycol, glycolate, 3‐hydroxypropionic acid, 1,2‐propanediol, 1,3 propanediol, 2,3‐butanediol, and isobutanol) and polyamide monomers (putrescine, cadaverine, gamma‐aminobutyrate, 5‐aminovalerate, succinate, and glutarate) .…”
Section: Introductionmentioning
confidence: 99%
“…These recombinant C. glutamicum strains simultaneously hydrolyze biomass and produce biochemicals such as succinate, l ‐lysine, and xylonic acid using released glucose, maltose, cellobiose, d ‐xylose, and l ‐arabinose from biomass (Fig. ) . Systematic engineering of metabolic pathways in C. glutamicum has allowed the biochemical production of novel products, such as platform chemicals (ethanol, ethylene glycol, glycolate, 3‐hydroxypropionic acid, 1,2‐propanediol, 1,3 propanediol, 2,3‐butanediol, and isobutanol) and polyamide monomers (putrescine, cadaverine, gamma‐aminobutyrate, 5‐aminovalerate, succinate, and glutarate) .…”
Section: Introductionmentioning
confidence: 99%
“…The Gram‐positive actinobacterium, Corynebacterium glutamicum , represents an attractive expression platform for secretory protein production in industrial biotechnology due to its ability to secrete proteins at the g L −1 range into the extracellular medium (Freudl, ; Ravasi et al, ; Watanabe, Teramoto, Suzuki, Inui, & Yukawa, ; Yim, Choi, et al, ). Furthermore, it is classified as GRAS (generally regarded as safe) organism and is the major producer for food and feed amino acids (Wendisch, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, extensive bioprocessing knowledge in an industrial environment as well as a comprehensive set of available genetic tools is available. Furthermore, C. glutamicum can be cultivated to high cell densities in fed‐batch cultivations (Knoll et al, ; Yim, An, Choi, Ryu, & Jeong, 2014; Yim, Choi, et al, ) and was shown to be very robust towards process inhomogeneities encountered in large scale cultivations (Käß et al, ; Limberg, Schulte, et al, ; Limberg, Pooth, Wiechert, & Oldiges, ).…”
Section: Introductionmentioning
confidence: 99%
“…These mostly monoderm bacteria are robust in terms of cultivation conditions, low nutritional demand, and are able to secrete proteins into the extracellular medium [3, 4]. Next to Bacillus  sp., a powerful expression host for the production of technical enzymes [5], Corynebacterium glutamicum is an attractive alternative host microorganism with demonstrated protein secretion capacity in the g/L-range [6, 7]. Also, extensive bioprocess knowledge with C.   glutamicum and methods for genetic manipulation are available because this microbe is a major producer for amino acids at industrial scale for decades [8].…”
Section: Introductionmentioning
confidence: 99%